Rasch Analysis of the Student Mental Health Scale (ISKM-R-2) - Lira Fessia Damaianti; Muhamad Arif Saefudin; Farhan Zakariyya; Helli Ihsan; Siti Chotidjah; Ghinaya Ummul Mukminin Hidayat; Aslama Tazkia; Atha Khalila Mustafid; Camila Azzahra Nurrohman; Nafisya Bulan Andari; Ni Kadek Ayu Regitha Pramesti (Universitas Katolik Soegijapranata, 2026)
Adolescent mental health is a critical issue, as this developmental stage is often marked by vulnerability to psychological problems, yet standardized measurement tools remain limited. This study aimed to evaluate the psychometric properties of the Student Mental Health Scale (ISKM-R-2) using the Rasch model. A methodological study design was adopted with a cross-sectional method, including 1,045 adolescents aged 15–19 years. The results suggested that the instrument had a multidimensional structure, with a two-factor model showing a better fit than the unidimensional model. Rasch analysis showed acceptable item fit and high reliability across dimensions. However, the instrument items were relatively difficult for the sample, as shown by the Wright Map analysis. The results of this study supported the importance of a multidimensional method in measuring student mental health and provided evidence for further refinement of the instrument.